Advanced Technology of Using Satellite Data Fuels in Agriculture - Choudhury, Swaralipi (Chronicle of Bioresource Management, 2024)
In this era of 21st century, the area of utilising smartphones and other digital technologies for better cultivation practices have been diversified world-wide. The use of spatial satellite images at variable frequencies and resolutions have paved a way towards modernisation of agriculture. An immediate requirement in this sector is a progressive farm analysis, crucial for providing precise data and a deep understanding to address areas where deficiency is lacking. Within this context, the burgeoning concept of ‘Smart Agriculture’ presented, which makes use of the modern technologies to improve the quality and quantity of agricultural products. This introduction has facilitated a way to decrease the human interventions and exploration of resource-efficient methods to achieve higher yield potentials. The advanced technology of satellite data fuels uses satellite data to monitor crop growth and other climate-related conditions, such as biomass, temperature and precipitation, to improve farm management.